2013
DOI: 10.1074/mcp.m112.019372
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Quantitative Proteomics of HeLa Cells Protein Species Using Stable Isotope Labeling with Amino Acids in Cell Culture(SILAC), Two-Dimensional Gel Electrophoresis(2DE) and Nano-Liquid Chromatograpohy Coupled to an LTQ-OrbitrapMass Spectrometer

Abstract: The proteomics field has shifted over recent years from two-dimensional gel electrophoresis (2-DE)-based approaches to SDS-PAGE or gel-free workflows because of the tremendous developments in isotopic labeling techniques, nano-liquid chromatography, and high-resolution mass spectrometry. However, 2-DE still offers the highest resolution in protein separation. Therefore, we combined stable isotope labeling with amino acids in cell culture of controls and apoptotic HeLa cells with 2-DE and the subsequent analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
119
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(131 citation statements)
references
References 52 publications
7
119
0
Order By: Relevance
“…Combined with enrichment techniques, 2-DE-MS and shotgun-MS may complement each other to characterize diverse forms of oxidation modifications [78]. However, multiple proteins can co-migrate in 2-DE, which means absolute quantification may not be possible [79]. In addition, hydrophobic proteins or proteins with high isoelectric point may be poorly resolved by 2-DE, although many of the earlier perceived limitations of 2-DE have now been either effectively addressed or established to be little more than dogma associated with poor sample handling and methodological practices.…”
Section: Two-dimensional Electrophoresismentioning
confidence: 98%
“…Combined with enrichment techniques, 2-DE-MS and shotgun-MS may complement each other to characterize diverse forms of oxidation modifications [78]. However, multiple proteins can co-migrate in 2-DE, which means absolute quantification may not be possible [79]. In addition, hydrophobic proteins or proteins with high isoelectric point may be poorly resolved by 2-DE, although many of the earlier perceived limitations of 2-DE have now been either effectively addressed or established to be little more than dogma associated with poor sample handling and methodological practices.…”
Section: Two-dimensional Electrophoresismentioning
confidence: 98%
“…To complicate things, a recent publication by Thiede et al ( 2013 ) demonstrated that ~50 % of 2-DE protein spots contained more than one identifi ed protein or protein species, using the most sensitive analytical methods available at present that included stable isotopic labeling with amino acids in cell culture (SILAC) and 2-DE-Orbitrap-LC mass spectrometry. This approach allowed the quantifi cation of proteins at the protein species level.…”
Section: A Biological Discourse On Protein Speciation -Starting With mentioning
confidence: 99%
“…The above outlined isotopic labeling/2-DE-Orbitrap-LC mass spectrometry method provided evidence for the existence of multiple HspB1 species, and, most importantly, also for their specifi c regulation during apoptosis in HeLa cells (Thiede et al 2013 ). By this approach ~1,200 proteins were identifi ed, together with ~2,700 protein species.…”
Section: Hspb1 Species-specifi C Regulation In Hela Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…It also seems that this scheme worked well in the case of uncomplicated proteomes, such as mycoplasma, for instance, where the expected numbers of proteoforms in proteomes were not so great as in mammalian cells [83,84,85,86]. After application of more sophisticated MS instruments for identification of proteins in 2DE spots (especially ESI LC-MS/MS), it was revealed that, depending on the gel resolution, the spots often contained more than a single protein, especially in the case of mammalian cells [87,88]. So, the quantitation of proteins became an ambiguous task.…”
Section: Decoding Of Information Hidden Inside the 2de Gelmentioning
confidence: 99%